Sustainability status of RSPO-certified and non-certified smallholder palm oil in Kotawaringin Barat Regency - Toyyibah, Toyyibah; Mulyo, Jangkung Handoyo; Jamhari, Jamhari (Agriekonomika, 2025)
Palm oil exhibits the highest oil productivity per hectare among vegetable oils and is priced more affordably than its counterparts. Consequently, palm oil has gained immense popularity and is currently the most extensively consumed vegetable oil. This condition has prompted a negative campaign against palm oil products, which are required to be produced sustainably. Community palm oil plantations are part of the palm oil agribusiness supply chain, which is also required to implement sustainability aspects. The objective of this study is to evaluate the sustainability of community palm oil plantations that are certified by the Roundtable on Sustainable Palm Oil (RSPO) and those that are not certified. This evaluation will be conducted using the Rap-Palmoil method, which employs index assessments across multiple dimensions, including economic, social, environmental, technological, and institutional aspects. The Multidimensional Scaling (MDS) method will be utilised for this analysis. The study was carried out in West Kotawaringin, which is located in a central district known for its palm oil fields. The data utilised comprises both primary and secondary sources. Primary data was acquired through interviews conducted with farmers, while secondary data was obtained from the central statistics agency and the plantation service. The participants in this study consisted of 60 farmers who were chosen by the snowball sampling method. The analysis using the criteria of Kavanagh Pitcher (2004) provided multidimensional results indicating that certified and uncertified community palm oil plantations fall under the "moderately sustainable" category. The sustainability index value for certified community palm oil plantations is higher, specifically 66.50, compared to 53.08 for uncertified ones. Based on each dimension, certified community palm oil plantations are classified as "moderately sustainable" in all aspects except for non-certified community palm oil plantations, which are categorised as less sustainable in two dimensions: environmental and institutional.